The effects of joint hypermobility on pain and functional biomechanics in adolescents with juvenile fibromyalgia: secondary baseline analysis from a pilot randomized controlled trial - William R. Black; Christopher A. DiCesare; Laura A. Wright; Staci Thomas; Megan Pfeiffer; Katie Kitchen; Tracy V. Ting; Sara E. Williams; Gregory D. Myer; Susmita Kashikar-Zuck (BMC, 2023)
Abstract Background Joint hypermobility is a common clinical finding amongst hereditary connective tissue disorders that is observed in pediatric rheumatological settings, and often associated with chronic pain. Joint hypermobility may also contribute to deficits in physical functioning and physical activity, but previous findings have been inconsistent. It is possible that physical activity impairment in joint hypermobility may be due to chronic aberrant movement patterns subsequent to increased joint laxity. Method As part of a larger randomized pilot trial of juvenile onset fibromyalgia (JFM), a secondary analysis was conducted to explore whether adolescents with JFM and joint hypermobility differed from non-joint hypermobility peers in terms of pain, daily functioning, and biomechanics (i.e., kinetics and kinematics) during a moderately vigorous functional task. Results From the larger sample of adolescents with JFM (N = 36), 13 adolescents (36.1%) met criteria for joint hypermobility and 23 did not have joint hypermobility. Those with joint hypermobility exhibited poorer overall functioning (Md = 20, Q 1 ,Q 3 [5.8, 7.6] vs. Md = 29, Q 1 ,Q 3 [5.1, 7.6]) but there were no differences in pain (Md = 6.9, Q 1 ,Q 3 [22, 33] , vs. Md = 6.45, Q 1 ,Q 3 [15, 29.5]). Inspection of time-series plots suggests those with joint hypermobility exhibited decreased hip flexion and frontal plane hip moment (e.g., resistance to dynamic valgus) during the landing phase (early stance) and greater hip and knee transverse plane moments during the propulsion phase (late stance) of the drop vertical jump task (DVJ). No other differences in lower extremity biomechanics were observed between study groups. Conclusions In this exploratory study, there were small but notable differences in biomechanics between patients with JFM who also had joint hypermobility versus those without joint hypermobility during a landing and jumping task (e.g., DVJ). These differences may indicate decreased joint stiffness during landing, associated with increased joint laxity and decreased joint stability, which may put them at greater risk for injury. Further study with a larger sample size is warranted to examine whether these biomechanical differences in patients with JFM and joint hypermobility affect their response to typical physical therapy or exercise recommendations.